2015
DOI: 10.5301/tj.5000224
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MicroRNA Expression Profile Identifies Novel Biomarkers for Non-small Cell Lung Cancer

Abstract: Our study may provide the groundwork for further clinical molecular target therapy experiments in NSCLC.BAC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 55 publications
5
30
1
Order By: Relevance
“…De-regulation of miRNA, such as miR-21, miR-22, miR-448, miR-654-3p, miR-205, miR-216a, miR-143, and miR-181a in NSCLC is a key factor underlying tumorigenesis (Wang et al, 2014;Xu et al, 2015). Human miR-204 is down-regulated in several tumor types, including NSCLC Shi et al, 2014;Xia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De-regulation of miRNA, such as miR-21, miR-22, miR-448, miR-654-3p, miR-205, miR-216a, miR-143, and miR-181a in NSCLC is a key factor underlying tumorigenesis (Wang et al, 2014;Xu et al, 2015). Human miR-204 is down-regulated in several tumor types, including NSCLC Shi et al, 2014;Xia et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…miRNA are important regulators that are significantly involved in the development of human diseases. Recent studies have shown a close correlation between dysregulated miRNA and carcinogenesis and cancer progression (Del Vescovo et al, 2014;Xu et al, 2015). For example,, and miR-125a-5p expression is associated with the progression and prognosis of non-small cell lung cancer (Kim et al, 2014;Zhu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the dysregulation of miRNAs is closely related to the development and progression of a number of cancers 4, 5, 12, 13, 21. The down‐regulation of miR‐138 in NSCLC has been consistently observed by multiple laboratories 16, 19.…”
Section: Discussionmentioning
confidence: 99%
“…The online literature database PubMed was used to identify lung cancer miRNA expression profiling studies published from January 2003 until May 2014 (last accessed on 15 May 2014), by means of the 'Medical Subject Heading' terms: 'NSCLC' and 'microRNAs' in combination with the keywords 'profiling' and 'humans'. The results of previous studies to identify circulating miRNAs specific to lung cancer were inconsistent (24)(25)(26)(27), and potential biomarkers remain to be elucidated and exploited. Based on these previous findings, a list of 15 miRNAs was compiled, whose expression has already been reported as deregulated in cancer, or has not been investigated (Table III).…”
Section: Methodsmentioning
confidence: 99%